Towards low-temperature laser paint stripping by photochemical mechanism on CFRP substrates. (6th January 2023) - Gu, Junyi; Su, Xuan; Jin, Yang; Li, Wenqin; Zeng, Zhihua; Zhang, Donghe; Xu, Jie; Guo, Bin
Abstract: Multilayer paint on the surfaces of carbon fiber-reinforced polymer (CFRP) composites was cleaned using an ultraviolet picosecond laser (λ = 355 nm) under different parameters. The surface morphology of the composite after paint removal was investigated by scanning electron microscopy (SEM), chemical composition and functional group detection by energy dispersive spectroscopy (EDS) and FT-IR, while the sample temperature was monitored by an infrared thermal imager during cleaning. Additionally, CFRP performances were evaluated before and after paint removal. These results demonstrated that after three cleaning cycles with 12 W laser power, the paint layers on CFRP is removed, the surface epoxy resin is retained, and the carbon fiber does not have any morphological damage. At the same time, the surface after de-painting also met the re-painting conditions, and the tensile strength was not degraded compared with the original sample. It is noteworthy that the UV picosecond laser shows "low temperature cleaning", which completely removes the paint layer on the CFRP surface at a temperature below 80 °C. This means that the paint stripping process will not cause potential thermal damage or degradation of mechanical properties for CFRP. Mechanism analysis indicated that the photochemical action led to the breaking of the chemical bond of the paint, thus achieving paint removal. This study demonstrates the feasibility of a laser cleaning process for de-painting from resin-based composite surfaces and guides the repair and maintenance of commercial aircraft. Highlights: The multi-layer coatings on the surface of aircraft composite skin were successfully removed by UV picosecond laser; Under proper parameters, the coatings was removed without any morphological damage to the carbon fiber; The UV picosecond laser realized low-temperature cleaning, with sample surface temperatures below 80 °C; The wetting angle and mechanical properties of the composites after laser cleaning were investigated.